Good outcomes in operative management of acquired prothrombin complex deficiency: a serial case report - Lola Purnama Dewi; Eka Nurfitri; Evodia Evodia; M. Tiya Romli (Indonesian Pediatric Society, 2011)
Background Acquired prothrombin complex deficiency (APCD) is a serious bleeding disorder in infants caused by idiopathic vitamin K deficiency. This disorder has a high mortality rate and sequelae are often seen in those that survive. The principal treatments are giving vitamin K and evacuating hemorrhages.Objective To report the outcome of surgical and non-surgical management in several cases of APCD.Method Eighteen infants diagnosed with APCD had similar histories: all were less than 4 months of age as well as exclusively breastfed, and none received vitamin K injections after birth. The diagnosis of APCD was made based on prolonged prothrombin times and proven intracranial hemorrhage on brain CT-scan. All subjects were treated with vitamin K injections for 5 days and offered craniotomy procedures.Results Out of 18 subjects, 10 underwent craniotomies, 9 within 48 hours of diagnosis and 1 on the fifth day of hospitalization. Two patients with small subdural hematomas were treated conservatively. Four subjects refused hospitalization. Two refused the craniotomy and died. All patients treated (12 cases), with both surgical and conservative treatment, were survived. Survivors were followed for 6 months and 10 of whom returned to the hospital for follow-up (9 patients who had operative procedures and 1 who did not). One patient who with craniotomy on the fifth day hospitalization had hydrocephalus as a sequela.Conclusion Operative procedure was needed for treatment of APCD in some cases with moderate until severe intracranial bleeding, while vitamin K injection only stop the progress of intracranial bleeding not as currable treatment of massive intracranial bleeding. [Paediatr Indones. 2011;51:298-302].